2009
DOI: 10.1002/etc.10
|View full text |Cite
|
Sign up to set email alerts
|

Dieldrin uptake and translocation in plants growing in hydroponic medium

Abstract: It has been known that the Cucurbitaceae family takes up a large amount of persistent organic pollutants from soils and that the translocation of those compounds in cucurbits is higher than those in non-cucurbits. To understand the persistent organic pollutant uptake mechanisms of plant species, we compared the dieldrin absorption and transportation potentials of several plants in hydroponic medium. Sorghum (Sorghum vulgare Moench), sunflower (Helianthus annuus L.), soybean (Glycine max), komatsuna (Brassica r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…The inverse relationship indicated that the acropetal transfer potential from roots to straws for short-chain PFAAs was higher than that for long-chain PFAAs, which may be due to the relatively large molecule and/or high lipophilicity of long-chain PFAAs when compared with short-chain PFAAs. It is suggested that the transport of POPs from roots to stems was mainly through transpiration (Murano et al, 2010;Collins et al, 2006;Burken and Schnoor, 1998). POPs with smaller size and lower lipophilicity are more easily translocated from root to shoot (Zhao et al, 2012;Satchivi et al, 2006).…”
Section: Accumulation Of Pfaas In Strawsmentioning
confidence: 99%
“…The inverse relationship indicated that the acropetal transfer potential from roots to straws for short-chain PFAAs was higher than that for long-chain PFAAs, which may be due to the relatively large molecule and/or high lipophilicity of long-chain PFAAs when compared with short-chain PFAAs. It is suggested that the transport of POPs from roots to stems was mainly through transpiration (Murano et al, 2010;Collins et al, 2006;Burken and Schnoor, 1998). POPs with smaller size and lower lipophilicity are more easily translocated from root to shoot (Zhao et al, 2012;Satchivi et al, 2006).…”
Section: Accumulation Of Pfaas In Strawsmentioning
confidence: 99%
“…The initial height of the solution surface was marked, and pre-aerated Hoagland nutrient solution was added every day to the marked line to replace any losses. The decrease in the amount of solution in one day was considered to be the transpiration rate (Murano et al, 2010). Exposure experiments of the three PBDEs were conducted separately to avoid the complexity resulting from PBDE debromination and volatilization.…”
Section: Hydroponic Exposurementioning
confidence: 99%
“…7,16) Further, Murano et al 17) suggested that protein-like materials in the xylem sap deliver dieldrin from the roots to the shoots. If these protein-like materials are photosynthetic products, the di erence in FCF with harvesting time can be explained.…”
Section: Relationship Between Dieldrin Concentrations In Cucumber Frumentioning
confidence: 99%
“…5) Dettenmaier et al 6) found that the transpiration stream concentration factor, which is the ratio of the contaminant concentration in the xylem sap to that in the hydroponic or soil solution surrounding the roots, showed a signi cant negative correlation with K ow . However, Murano et al 7) reported that the roots of all plant types studied (cucurbits, sorghum, sun ower, soybean, and komatsuna) contained dieldrin, whereas only the cucurbits (white-owered gourd, cucumber, and zucchini) contained considerable amounts of dieldrin in their shoots when grown in a hydroponic medium. Otani et al 8) found that only the cucurbits took up dieldrin, and uptake by plants of the other 16 families was small or negligible when grown in dieldrin-contaminated soil.…”
Section: Introductionmentioning
confidence: 97%